Flourishing in University Students in Indonesia in terms of Self-Compassion - Asrowi Asrowi; Elwas Berdha Krismona; Zulfia Azzahra; Astri Rachmahyani; Pau Kee (Universitas Sebelas Maret, 2026)
Flourishing can be understood as a state of well-being and optimal happiness experienced by an individual. Various factors contribute to flourishing, with self-compassion being a significant one. This study aims to investigate the impact of self-compassion on individual flourishing. A quantitative, correlational approach was utilized. The participants were 170 undergraduate students from Indonesia. Data were analyzed using a simple linear regression test, which yielded a significance value of 0.000, well below the threshold of 0.05. These results indicate that self-compassion has a significant effect on individual flourishing. Furthermore, the coefficient of determination (R-square) for self-compassion was 0.264, suggesting that self-compassion accounts for 26.4% of the variance in flourishing. These findings underscore the importance of fostering self-compassion to enhance individual flourishing.